(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
The quality of surgical outcomes in hepatic echinococcosis is critically dependent on two pre- and perioperative determinants that remain inadequately standardized in many endemic regions: accurate multimodal imaging classification and rigorously structured antiparasitic chemotherapy